The Effect of Using Gamification to Improve EFL Students’ Academic Performance - Tayeh, Qadri; Krishan, Tamara Moh’d; Malkawi, Nibal (Journal of Ecohumanism, 2024)
This paper aims to determine whether there is evidence that gamified instruction can be effective in improving EFL students’ academic achievement. The aim of the research is to establish how effective gamification is as a method against more traditional types of education and what areas of the English language—for example, reading comprehension, grammar, and vocabulary—are most effectively promoted via the integration of gamification into the classroom environment. The sample included 120 fourth graders from public schools in Jordan, where 60 children were to form the gamified instruction group and another 60 to form the standard instruction group. Pretests and posttests of English language skills using standardized tools measured students at two different times: before and after the instructional interventions. These tests are the main instruments utilized for data collection and analysis. Independent t-test, one-way ANOVA, and one-way MANOVA tests were performed to test the variation and holistic impact of the instructional methods on different components of language learning. The experimental findings support that the gamified instruction group scored significantly higher than the regular instruction group at post-intervention. More specifically, the students of the game-based group scored an average of 74.44 (SD= 7.93) on the posttest, compared to 69.31 (SD = 6.14) for those of the control group. The result for the T-test yields t = 4.05 and p < 0.001, hence showing that the gamified group had significantly better results. The classroom gamification usage made noteworthy gains in students’ vocabulary, grammar, and reading comprehension abilities. One-way ANOVA results were vocabulary, F = 22.65, p < 0.001; grammar, F = 15.78, p < 0.001; and reading comprehension, F = 18.93, p < 0.001. MANOVA supported this finding that the Wilks’ Lambda value was 0.62, with an F-value of 20.45 and a p-value less than 0.001, indicating that gamified training was of benefit overall in enhancing English language competence. The results of this research come with a very exciting revelation, such as gamified instruction being an excellent means of teaching English as a foreign language since it enhances students’ interest and performance in class.